2022
DOI: 10.3390/geriatrics7010013
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Open-Label Study to Assess Efficacy of Weekly Assumption of Cholecalciferol versus Calcifediol in Older Patients with Hypovitaminosis D

Abstract: The aim of this single-center, open-label, randomized controlled study was to evaluate which formulation of vitamin D—between cholecalciferol and calcifediol—is most effective in the treatment of hypovitaminosis D in older adults. Demographic characteristics, clinical history, and comprehensive geriatric assessment were recorded at admission. Eligible patients were randomly assigned an equivalent vitamin D supplement, either with cholecalciferol or calcifediol, from the time of hospital admission to three mont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The oral administration of 20 μg of calcifediol compared to 800 IU (20 μg) of cholecalcifeol was significantly more effective and faster in increasing serum 25OHD concentrations in postmenopausal women in the range above 30 ng/mL; furthermore, it produced significantly more pronounced suppression of eotaxin, IL-12, monocyte chemoattractant protein 1 MCP-1, and macrophage inflammatory protein 1 beta MIP-1β [96], which are markers implicated in the severity of COVID-19 [97]. Treatment with calcifediol prescribed for whatever health reason, such as osteoporosis, improves the 25OHD status [87,98], and thus may reduce the risk and impact of COVID-19 [53]. Indeed, in a retrospective cohort study in the Barcelona area (Spain) on a population of 4.6 million inhabitants collected in the public health system registries, from Calcifediol's ease of absorption and availability is especially relevant in patients with severe fat malabsorption [89].…”
Section: Calcifediol Treatment For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The oral administration of 20 μg of calcifediol compared to 800 IU (20 μg) of cholecalcifeol was significantly more effective and faster in increasing serum 25OHD concentrations in postmenopausal women in the range above 30 ng/mL; furthermore, it produced significantly more pronounced suppression of eotaxin, IL-12, monocyte chemoattractant protein 1 MCP-1, and macrophage inflammatory protein 1 beta MIP-1β [96], which are markers implicated in the severity of COVID-19 [97]. Treatment with calcifediol prescribed for whatever health reason, such as osteoporosis, improves the 25OHD status [87,98], and thus may reduce the risk and impact of COVID-19 [53]. Indeed, in a retrospective cohort study in the Barcelona area (Spain) on a population of 4.6 million inhabitants collected in the public health system registries, from Calcifediol's ease of absorption and availability is especially relevant in patients with severe fat malabsorption [89].…”
Section: Calcifediol Treatment For Covid-19mentioning
confidence: 99%
“…Treatment with calcifediol prescribed for whatever health reason, such as osteoporosis, improves the 25OHD status [87,98], and thus may reduce the risk and impact of COVID-19 [53]. Indeed, in a retrospective cohort study in the Barcelona area (Spain) on a population of 4.6 million inhabitants collected in the public health system registries, from April 2019 to February 2020, the risk of COVID-19 infection during the first wave of the pandemic was assessed in patients who were prescribed cholecalciferol (n = 108,343) or calcifediol (n = 134,703) during the previous 4 months and were compared with propensity score-matched untreated controls [99].…”
Section: Calcifediol Treatment For Covid-19mentioning
confidence: 99%
“…The group was ignored as supplementation pattern was less frequent than weekly. Background vitamin D intake: NR Background calcium intake: NR Compliance NR Serum 25(OH)D: measured by HPLC and ultraviolet detection method time of blood collection after last dosage: NR Serum PTH: measured by ECLIA (Roche Diagnostic) Data extracted: unclear Serum 25(OH)D at 6mo (nmol/L) G1: 80.0 ± 2.0 G2: 161 ± 21.7 G3: 213.5 ± 80.0 Serum 25(OH)D at 12 mo (nmol/L) G1: 86.2 ± 23.7 G2: 188.0 ± 24.0 G3: 233.0 ± 81.2 Serum 25(OH)D, change over 12 mo (nmol/L) G1: 45.7 ± 19.5 G2: 150.8 ± 22.3 G3: 195 ± 79.3 Serum PTH at 6 mo (ng/L) G1: 46.5 ± 11.2 G2: 38.7 ± 10.7 G3: 35.4 ± 8.4 Serum iPTH at 12 mo (ng/L) G1: 41.6 ± 10.5 G2: 32.5 ± 8.8 G3: 29.0 ± 5.9 3 Okoye et al. (2022) Italy Latitude [assumed] 43.7° N From hospital admission to 3 mo after discharge. Unclear funding [stated no external funding received] RCT (parallel) Inclusion criteria: Geriatric patients consecutively hospitalized in the Geriatric Unit of the University Hospital of Pisa for acute illness, with 25(OH)D 3 levels <30 ng/mL [<75 nmol/L]. Exclusion criteria: Having received vitamin D supplementation during the past 6 mo; stage V renal insufficiency; liver failure (defined as a Child–Pugh classification of a B or C); hyperparathyroidism; malabsorption syndromes or the long‐term prescription of drugs reducing vitamin D absorption (i.e., antiepileptic drugs, long‐term corticosteroids, or bisphosphonates); neoplastic disease under treatment; patients being unable to give informed consent. N participants randomised/completed/analysed G1: 89/69/69 G2: 89/70/71 Sex (% females) G1: 56.5 G2: 59.1 Age (y): G1: 84.9 ± 6.4 G2: 82.7 ± 6.7 Plasma 25(OH)D 3 (ng/mL) G1: 16.8 ± 9.9 ng/mL [42.0 ± 24.75 nmol/L] G2: 18.8 ± 13.3 ng/mL [47.0 ± 33.25 nmol/L] PTH (ng/dL) G1: 48.1 ± 39.6 G2: 60.7 ± 36.9 BMI (kg/m 2 ) G1: 23.7 (7.2) G2: 25.0 (5.6) Ethnicity [assumed]: Majority Caucasian Smoking status: NR Alcohol use: NR Health status (%) Arterial hypertension: G1: 69.6 G2: 70.4 Coronary heart disease: G1 11.6 G2: 9.9 Atrial fibrillation: G1: 17.4 G2: 19.7 Heart failure: G1: 42.0 G2: 39.4 Diabetes: G1: 20.3 G2: 21.1 Chronic kidney disease: G1: 23.2 G2: 22.5 Chronic obstructive pulmonary disease: G1: 8.6 G2: 9.8 Season: May to Sept 2020 Doses G1: vitamin D 3 437.5 μg/wk [=62.5 μg/d] G2: calcidiol 140 μg/wk [=20 μg/d] Background vitamin D intake: NR Background calcium intake: NR Compliance Pill count method: Complete adherence stated. Plasma 25(OH)D 3 : measured by HPLC–MS/MS time of blood collection after last dosage: NR PTH: method of measurement NR Data extracted: unclear Plasma 25(OH)D 3 at 3 mo (ng/mL) G1: 30.7 ± 8.4 ng/mL [76.75 ± 21.0 nmol/L] G2: 45.4 ± 9.8 ng/mL [113.5 ± 24.5 nmol/L] PTH at 3 mo (ng/dL): NR 3 Ruggiero et al. (2019) Italy Latitude [assumed] 43.1° N From hospital admission to 7 mo after discharge. Unclear funding [stated no external funding received] RCT, pragmatic (parallel) Inclusion criteria: Community‐dwelling women and men, oldest‐old patients, aged >75 years, consecutively admitted to geriatric acute care ward. Exclusion criteria: On treatment with vitamin D, multivitamins, calcium supplements, anti‐fracture drugs or steroids; suffered from fragility fractures within 6 mo, cancer within 5 y, hyperparathyroidism, hypercalcaemia, hypercalciuria, hypoph...…”
Section: Appendix C – Evidence Tables For the Studies Includedmentioning
confidence: 99%
“…No studies were identified as being influential based on leave out analysis. Excluding the three studies in RoB Tier 3 (Catalano et al, 2015;Navarro-Valverde et al, 2016;Okoye et al, 2022) had little impact on the results: ROM (95% CI) was 2.36 (1.82, 3.10) and heterogeneity remained high (Figure 3c). Since the dose-response curve between the intake of vitamin D 3 and serum 25(OH)D concentration tends to level-off gradually at high intakes, a sensitivity analysis was conducted excluding the two RCTs that used ∼ 60 μg/day vitamin D 3 as the reference dose (Figure 3d).…”
Section: Effect Of Calcidiol Monohydrate Versus Vitamin D 3 On Serum ...mentioning
confidence: 99%
See 1 more Smart Citation